The Initiated of Formation of Linking Social Capital of Community in Creative Tourism Village Dago Pojok, Bandung, West Java Province, Indonesia - Alfrojems Alfrojems; RR E Sulistyaningsih; Triyanti Anugrahini; Adhi Karyono (Asian Social Work Journal, 2021)
Poverty in rural areas is now reaching an alarming condition, according to the Central Statistics Agency at this time the poor in rural areas dominate the percentage of poverty in Indonesia by 60%. Efforts to improve the welfare of rural communities will not be separated from how people use and maximize their potential, especially in networking relevant to the issue of social capital. Based on the concept of social capital, there is currently a type of social capital linking, which means emphasizing how the community is able to build relationships with parties who have authority, especially in making policy. This is considered to be important to support the development of welfare for the community, especially in the Dago Creative Tourism Village. Based on this, the purpose of this study is how the community initiated the development of social capital linking in the community in Dago Creative Tourism Village. Therefore, based on these objectives, this study uses a qualitative approach with a descriptive type. The data collection is done by observation, study of documentation of relevant documents and interviews. In addition interviews were conducted on 15 informants obtained using purposive sampling technique to determine informants. The results of this study indicate that there are several ways in which people initiate government involvement in developing social capital linking, such as community legalizing organizations, people participating in activities organized by the government, and the community providing government opportunities to participate in every activity organized by the government